Investigación de mercados emergentes para la exportación de piña Colombiana (2022)
This research monograph is focused on expanding pineapple trade internationally, allowing to find new alternatives in emerging markets. For the development of possible export processes, the analysis of several market variables is carried out, resulting in the identification of new partner. For the research development, descriptive statistics are used, where the necessary information is collected to identify the pineapple market behavior, showing relevant data that allows recognition of the main importers and emerging markets. Determining that France, Canada, and Curaçao present the best opportunity for an eventual export since that the demand between 2014-2021 has increased.